The Need for Developing Principal Supervision Through a Canva-Based Bagja Coaching Approach to Improve Teacher Professionalism in Pemalang Regency - Surawan Nurhidayat; Sitti Hartinah; Khusnul Khotimah (Journal of General Education and Humanities, 2026)
This study aims to develop a principal supervision model using a Canva-based BAGJA Coaching approach to improve the professional competence of elementary school teachers in Pemalang Regency. The study employed a Research and Development (R&D) method using the 4D development model, consisting of the Define, Design, and Develop stages, with the development process limited to the Develop stage due to research scope and time constraints. The research was conducted in several primary schools within the KWK Ulujami area, Pemalang Regency, selected through purposive sampling based on school readiness and the need for academic supervision implementation. The research population consisted of 70 primary school teachers, with 56 teachers and several school principals involved as research subjects, while the research object was the Canva-assisted BAGJA Coaching-based principal supervision model. Data were collected through semi-structured interviews, observation of supervision implementation, expert validation, and user response questionnaires. The research instruments included interview guidelines, observation sheets, expert validation sheets from material, media, and supervision experts, and practicality and effectiveness questionnaires. Data analysis was conducted using a mixed-methods approach, with qualitative data analyzed using the Miles and Huberman technique and quantitative data analyzed using descriptive statistics. The results showed that the developed supervision model was highly feasible in terms of content validity, media design, and applicability. Limited trials indicated increased teacher activeness in reflective practices and more participatory supervision processes. The study concludes that the Canva-assisted BAGJA Coaching-based principal supervision model has strong potential as an alternative supervision strategy that meets the demands of education in the digital era and effectively enhances elementary school teachers’ professional competence.